Pemikiran pendidikan karakter profetik Muhammad Natsir (FACTUM: Jurnal Sejarah dan Pendidikan Sejarah, 2024)
The purpose of the article is to know the background of Muhammad Natsir in the field of education and knows how the concept of prophetic qualification in the thoughts of Muhammad Natsir. The method used in writing this scientific article is a qualitative deal with a historical approach to the stages of topic selection, heuristics, source criticism, interpretation, and historiography. Muhammad Natsir is an educational thinker in addition to a politician. He has a prophetic education thought studied in three pillars, namely transcendence, humanization, and liberation. In the context of educational transcendence, it founds in tauhid, and qualification directed to form people who have faith, godly, noble, advanced, and independent. While in the context of humanization establishes a life ethic and the unity of people that can perfect human nature. Whereas in the context of liberation, education functions as liberation by endeavoring and consistently to humanize humanity and actualize themselves. Then the three pillars are implemented in an integral system by combining religious and general science. Through prophetic education, social change can occur towards a civilized and noble nation and bring progress to the state
Keywords: History; Muhammad Natsir; Prophetic education; Three pilladrs